Otimização do procedimento de solubilização de rochas silicáticas em recipientes abertos para análise por ICP-AES - Bahia Filho, Oscar [UNESP]; Moreno, Maria Margarita Torres [UNESP]; Nardy, Antonio José Ranalli [UNESP]; De Oliveira, Marcos Aurélio Farias [UNESP]; Da Silva, José Ângelo Ferreira [UNESP] (My University, 1996)
The main variables found on procedure of the dissolution silicate rocks using acid dissolution in teflon open vessel for analysis of micro elements by ICP-AES has been determined. The results obtained for some samples showed strong dependence of the rock mineralogical composition, then it was recommended an alkaline fusion step after acid dissolution. The decomposition procedure use 20 ml of an acid mixture of HF:HNO3 in the proportion 3:1 for a fraction of 250 mg pulverized sample. The recommended temperatures were 60°C for attack and 90°C for acid volatilization. The fusion step with 50 mg LiBO2 at 1000°C may be used if non-attacked residue is observed in the solution. The whole time was 6 h per sample. Nine types os silicate rocks that show mineralogical and chemical different compositions were chosen for obtaining the optimization of the variables. The elements used were Ce, Y, Yb and Zr. In addition, ultrassonic nebulization has been used. The percentual standard deviations obtained for five determinations were 0.7 and 1.4 for triplicate samples. The mineralogical and textural information from the petrographical analysis of the samples indicated the need of increasing the fusion step on the optimized procedure.
Procedure optimization of silicate rocks dissolution in open vissels for ICP-AES analysis
Keywords: Analytical geochemistry; Dissolution of geological matrix; Inductively coupled plasma atomic emission spectrometry; Silicate rock analysis; Ultrassonic nebulization